Herbal remedies for liver fibrosis: A review on the mode of action of fifty herbs - Latief, Uzma (J Tradit Complement Med, 2017)
Liver fibrosis is a dynamic pathological condition which can be slowed down in its initial phases. Without proper clinical management of fibrosis, progressive liver damage may lead to cirrhosis and ultimately to liver failure or primary liver cancer, which are irreversible conditions. Therefore, in order to cure fibrotic damage to liver, its early stages should be the centre of attention. In this context, some supplements and ‘complementary and alternative medicine (CAM)’ deserve specific mention, because of their already recognized natural way of healing and long lasting curative effects. Moreover, CAM display negligible side effects and hence it is gaining worldwide importance in clinical practices. In particular, herbal medicines are now replacing synthetic pharmaceuticals and looked upon as the sources of novel bioactive substances. To develop satisfactory herbal combinations for treating liver fibrosis, phytoproducts need to be systematically evaluated for their potency as anti-fibrotic, anti-hepatotoxic and antioxidant agents. More importantly, the identified herb/agent should have the remarkable tendency to stimulate hepatocytes regeneration. The present review is a systematic account of at least fifty medicinal herbs and their products which in experimental models have demonstrated antifibrotic activity and thus, most likely candidates to offer therapeutic protection to liver. Nevertheless, much additional work is still needed to explore molecular pathways to discover potential applications of these medicines so as to open up new vistas in biomedical research.